Morfologi Spermatozoa Itik Lokal (Anas platyrhyncos) Pasca Preservasi Dalam Medium Berbeda Dikombinasi Krioprotektan Kuning Telur - Atifah, Yusni (BIOLINK (Jurnal Biologi Lingkungan, Industri, Kesehatan), 2018)
The aim of this study was to assess the percentage of local duck spermatozoa morphology (Anas platyrhynchos) for 6 days of storage in three storage mediums combining various egg yolk (EY) concentrations.This experimental study applied three combinations of factors as treatment. Medium (Tris, PBS or Ringer lactate), egg yolk (EY) concentration 0,5,10,15 or 25% and storage time (0,1,2,3,4,5,6 day). Spermatozoa obtained by sequence method, ejaculate or sperm obtained in swim up in medium, swim up spermatozoa were used for treatment in storage medium according to treatment and assessed before and after morphology of storage in refrigerator temperature (50 C). The results showed that spermatoza morphology was significantly different (P <0.01) between 15 treatments. The medium factor and concentration of EY significantly (P <0.05) affected the morphology of treatment spermatozoa. The highest percentage of highest post-preservation spermatozoa morphology for six days was obtained in 5% yolk treatment in PBS medium (5EYPBS). This study proves that egg yolk cryoprotectants are good for maintaining the morphology of local duck spermatozoa.